2017
DOI: 10.4314/ijbcs.v11i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter study on antibiotic susceptibility/resistance trends in the western region of Cameroon

Abstract: In the global frame aiming at assessing bacterial susceptibility for safer and cost-effective healthcare, the present survey was conducted in three hospitals: Bafoussam Regional Hospital (BRH), Bangwa Protestant Hospital (BPH) and Bangangté District Hospital (BDH). Sampling was performed by fingerprinting on culture media and swabbing of hospital devices or surfaces. Wards of interest included: Pediatrics, Medicine, Operating Theater, Intensive Care Unit, Maternity, and, in the BDH, Laboratory in addition. Cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…Of these 66 studies included in the review, 52 were rated as good quality (low risk of bias) and 14 were of moderate quality (medium risk of bias). A total of 45 studies reported on the outcome of antibiotic resistance in humans [15, 27–69], 9 reported on the outcome of antibiotic resistance in animals [70–78] and 12 on the environment [9, 15, 16, 57, 62, 64, 75, 79–83] (Table 1). Five studies reported outcome of antibiotic resistance in both human and environment while one study reported on the outcome of antibiotic resistance for animals, humans and environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 66 studies included in the review, 52 were rated as good quality (low risk of bias) and 14 were of moderate quality (medium risk of bias). A total of 45 studies reported on the outcome of antibiotic resistance in humans [15, 27–69], 9 reported on the outcome of antibiotic resistance in animals [70–78] and 12 on the environment [9, 15, 16, 57, 62, 64, 75, 79–83] (Table 1). Five studies reported outcome of antibiotic resistance in both human and environment while one study reported on the outcome of antibiotic resistance for animals, humans and environment.…”
Section: Resultsmentioning
confidence: 99%
“…Also, a small repertoire of generic antimicrobials which are often poor quality [13], sold in open markets with little or no regulations, quality control and inappropriate prescription practices [13, 14], are regularly used. Poor personal and environmental hygiene practices have favored the spread of drug resistant pathogens within the hospital environment, causing hospital-acquired infections [15, 16]. The use of antimicrobials as growth promoters in agriculture has been associated with resistant food borne pathogens and relatively risky to human, animal and environmental health [17].…”
Section: Introductionmentioning
confidence: 99%
“…Ngassam et al, in a study conducted in the same locations as ours (Bafoussam Regional Hospital, Bangangté District Hospital, and Cliniques Universitaires des Montagnes) found a high contamination rate of isolates collected with a predominance of Bacillus and Staphylococcus. Susceptibility profiles also indicated high resistance rates (Ngassam et al, 2017).…”
Section: Antibiotic Susceptibilitymentioning
confidence: 99%
“…Many quinolones display interesting pharmacological activities and have found applications as pharmaceuticals, e.g antimalarial drugs, such as quinine or chloroquin (Jayashree et al, 2012). The present therapeutic arsenal notwithstanding, the efficacy of existing antimicrobial molecules is limited by the increasing multi-drug resistant microbes (Akpa et al, 2016) which is among the prime factors that ensures success of adaptive somatic modifications for enhanced living of these pathogens (Ngassam et al, 2017).…”
Section: Introductionmentioning
confidence: 99%